Identical Ciguatoxin-3C group profiles in Lutjanus bohar from the Pacific and Indian Oceans - indicating the need to re-evaluate geographical CTX classifications - Spielmeyer, Astrid; Loeffler, Christopher R.; Kappenstein, Oliver (Frontiers in Marine Science, 2022)
Ciguatoxins (CTXs) are a group of marine biotoxins, consisting of over 30 different congeners that can contaminate marine food webs. Generally, the molecular structures among the known congeners are variable by geographical region (i.e., ocean basin) and vector species. Limited information is available regarding the CTX profiles among or within CTX vector species and their capture regions. Within this study, an in-depth investigation based on a semi-targeted LC-MS/MS approach was conducted to investigate 52 tissue samples from a single species Lutjanus bohar (Lutjanidae), a common CTX vector, sourced from two distinct regions (Indian Ocean and Pacific Ocean). All samples revealed the presence of a complex CTX contaminant profile, with samples containing several congeners of the CTX3C-group (2,3,51-trihydroxyCTX3C, 2,3,-dihydroxyCTX3C, 2-hydroxyCTX3C, M-seco-CTX3C, 51-hydroxyCTX3C, CTX3C, and respective 49-epimers in most cases). All samples were previously found to possess a CTX-like toxicity within an in vitro cytotoxicity assay (N2a-bioassay), demonstrating the relevance of CTX3C-group congeners with regard to ciguatera poisoning. Individual samples contained an indistinguishable toxin profile within the species and among the distinct oceanic capture regions. These findings imply either a species-specific CTX metabolism or the emergence of an interoceanic CTX toxin profile. The inter-regional CTX profile demonstrated here provides further evidence that classifying CTX congeners based on ocean basins may be imprecise.